Current perspectives on the hormonal control of seed development in Arabidopsis and maize: a focus on auxin - Locascio, Antonella; Roig-Villanova, Irma; Bernardi, Jamila; Varotto, Serena (Frontiers in Plant Science, 2014)
The seed represents the unit of reproduction of flowering plants, capable of developing into another plant, and to ensure the survival of the species under unfavorable environmental conditions. It is composed of three compartments: seed coat, endosperm and embryo. Proper seed development depends on the coordination of the processes that lead to seed compartments differentiation, development and maturation. The coordination of these processes is based on the constant transmission/perception of signals by the three compartments. Phytohormones constitute one of these signals, gradients of hormones are generated in the different seed compartments, and the ratios of which constitute the signals that induce/inhibit a particular process in seed development. Among the hormones, auxin seems to exert a pivotal role; since it is the unique hormone that maintains high level of accumulation from fertilization to seed maturation. The gradient of auxin generated by its PIN carriers, affects several processes of seed development, including pattern formation, cell division and expansion. Despite the high degree of conservation in the regulatory mechanisms that lead to seed development within the Spermatophytes, remarkable differences exists during seed maturation between Monocots and Eudicots species. For instance, in Monocots, the endosperm persists until maturation, and constitutes an important compartment for nutrients storage; while in Eudicots it is reduced to a single cell layer, as the expanding embryo gradually replaces it during the maturation. This review will provide an overview of the current knowledge on hormonal control of seed development, by considering the data available in two model plants: Arabidopsis thaliana,for Eudicots, and Zea mays, for Monocots. We will emphasize the control exerted by auxin on the correct progress of seed development comparing, when possible, the two species.